Hepatoprotective Potentials of Dates Extract (Phoenix dactylifera) in Acetaminophen-Induced Mice - Andriyanto Andriyanto; Hamdika Yendri Putra; Sharon Aurelia; Aulia Andi Mustika; Wasmen Manalu; Mawar Subangkit; Elpita Tarigan; Yusa Irarang (Majalah Kedokteran Bandung, 2023)
Dates (Phoenix dactylifera) are considered as a well-known fruit consumed by many people in various countries. This study aimed to examine potential effects of dates as a hepatoprotective agent in mice. This study was conducted at the Iratco Group’s eLRosa Laboratory Research Facility, Indonesia, starting from June 2022 to July 2022. Mice from ddY strain were randomly divided into 5 groups (n=5 per group) of positive and negative control groups, and treatment groups 1, 2, and 3. The negative control group as the normal baseline did not receive acetaminophen and date extract. In treatment groups, 30 µL/30 gr BW, 60 µL/30 gr BW,  and 100 µL/30 gr BW extract was given per oral to Treatment Group 1, Group 2, and Group 3, respectively for 20 days. On day 21, all  treatment groups were induced with 300mg/KgBW acetaminophen for 3 days via the intraperitoneal route. Blood tests were performed on day 24 to measure the serum transaminase level as the parameter of liver damage. The lowest level of transaminase serum was found in group 3 with the highest volume of dates extract, which was 100 µL, followed by group 2 (60 µL), and group 1 (30 µL). There was a significant difference between the positive control group and treatment groups with  no significant difference was seen between negative and the treatment groups. This study concludes that dates extract has the potential of being a hepatoprotective agent.